CATEGORY SHIFTS IN THE INDONESIAN TRANSLATION OF THE DIALOGUE IN NOVEL IT STARTS WITH US - Nurul Jannah, Rahmadani; Sega Kendenan, Esriaty (Bajang Institute, 2025)
This research was conducted to identify the categories of translation shifts in a dialogue between Lily and Ryle in the novel It Starts With Us by Colleen Hoover (SL) and its Indonesian version Awal Di Antara Kita, translated by Eka Budiarti (TL). The researcher used a descriptive qualitative method to analyze the text in the novel. Several types of translation shifts were found in the emotional tension dialogues between Lily and Ryle. The most dominant category was unit shift, with 15 instances (75%), followed by intrasystem shift with 3 instances (15%), and class shift with 1 instance (5%). This study is expected to be useful for those interested in conducting research on translation shifts